Gand : apologie d'une ville rebelle : histoire Art Culture - Balthazar, Herman; Boone, Marc; Coppejans-Desmedt, Hilda; Daenens, Lieven; De Baere, Bart; Decavele, Johan; Declercq, Georges; Dhanens, Elisabeth, 1915-2014; Duverger, Erik; Hoozee, Robert; Laleman, Marie Christine, 1952-; Lesaffre, Micheline; et al. (Antwerpen : Mercatorfonds, 1989)
Burssens, Jan ; Copers, Leo ; de Cordier, Thierry ; Cortier, Amédée ; Debaere, Hugo ; Dujourie, Lili ; Heyvaert, René ; Van Isacker, Philip ; De Keyser, Raoul ; Landuyt, Octave ; Matthys, Danny ; Raveel, Roger ; Van Den Berghe, Roland ; Van Severen, Dan ; Van Snick, Philippe ; Vandenberg, Philip ; Vercruysse, Jan
Frans
boek
Keywords: Gent